VIDAS TEST OF IgG AVIDITY FOR DETECTION OF ACUTETOXOPLASMOSIS IN THE EARLY PREGNANCY - Zgaeir, Khawla; Al-Qadi, Ban; Al-Djaily, Khitam (Iraqi Journal of Science, 2024)
Toxoplasmosis is usually asymptomatic, but can have severe consequences if itoccurs in immunodeficient subject or fetuses. The diagnosis of toxoplasmosis duringpregnancy is often based on maternal serological testing for IgM and IgG anti-Toxoplasma antibodies. Persistence of IgM for long periods, posses’ problems indistinguishing acute from chronic infection. The evaluation of specific IgG avidityenables more accurate dating, since avidity rises progressively during the course ofinfection.Seventy six women in the first 16 weeks of pregnancy were tested for VIDAS IgM,IgG antibodies and VIDAS toxo-IgG avidity. Low avidity antibodies weredemonstrated in 2 (33.3%) of 6 sera positive with IgM assay and 4 (12.12%) of serapositive with IgG assay. Low avidity was also detected in 2 (3.27%) of 61 seranegative with IgM. The low avidity suggesting a recent infection, while high avidityin 3 (50%) of the 6 positive IgM and 24 (72.72%) of 33 positive IgG indicating thatthe infection acquired in the distant past. These findings highlight the value ofVIDAS IgG avidity when used in combination with the VIDAS IgM and IgG assaysto provide a confirmatory evidence of an acute infection with a single serumspecimen for pregnant women.